2021
DOI: 10.1001/jamanetworkopen.2021.38526
|View full text |Cite
|
Sign up to set email alerts
|

Association of Physical Activity Level With Risk of Dementia in a Nationwide Cohort in Korea

Abstract: IMPORTANCE Current guidelines recommend 500 to 999 metabolic equivalent (MET)-minutes per week (MET-min/wk) of regular physical activity. However, evidence regarding the association between light-intensity physical activity (LPA) and dementia in older adults is inconsistent. OBJECTIVE To assess the association between physical activity and new-onset dementia, focusing on the dose-response association between physical activity and dementia and the association of LPA with the incidence of dementia. DESIGN, SETTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…Actually, achieving > 150 min/week of moderate-intensity aerobic exercise was associated with at least a 30% lower risk of morbidity, mortality, disability, frailty, and dementia compared with being inactive 23 . Our previous study also showed that increasing levels of physical activity were associated with a gradual decrease in the risk of dementia, and even a low amount of light-intensity physical activity was associated with reduced dementia risk 24 . Our results are consistent with previous studies and highlight the importance of the role of CVH, in particular physical activity, in promoting brain health at older ages.…”
Section: Discussionmentioning
confidence: 62%
“…Actually, achieving > 150 min/week of moderate-intensity aerobic exercise was associated with at least a 30% lower risk of morbidity, mortality, disability, frailty, and dementia compared with being inactive 23 . Our previous study also showed that increasing levels of physical activity were associated with a gradual decrease in the risk of dementia, and even a low amount of light-intensity physical activity was associated with reduced dementia risk 24 . Our results are consistent with previous studies and highlight the importance of the role of CVH, in particular physical activity, in promoting brain health at older ages.…”
Section: Discussionmentioning
confidence: 62%
“…Eight studies ( Lee A. T. C. et al, 2015 , 2018 ; Kishimoto et al, 2016 ; Zhou et al, 2017 ; Dupré et al, 2021 ; Fajersztajn et al, 2021 ; Sato et al, 2021 ; Yoon et al, 2021 ) investigated the effect of leisure activities on dementia in older adults. The I 2 was 97.1%.…”
Section: Resultsmentioning
confidence: 99%
“…The environmental component of ARCD and ARD is well-established in large cohort studies in multiple countries but has yet to form the basis of ARD prevention or treatment policies [ 10 , 37 , 38 , 39 , 40 ]. This includes significantly increased risk of ARCD and ARD as well as worse cognitive function associated with sedentary behavior and reduced physical activity [ 37 , 41 , 42 , 43 ], chronic sleep deprivation or sleep disruption [ 37 , 44 , 45 ], insulin resistance and dysglycemia [ 46 , 47 ], poor-quality nutrition and associated changes in nutrient status [ 10 , 48 ], body composition [ 49 , 50 , 51 , 52 ], sex hormone status during and after the menopausal transition [ 53 ], and the effect of social isolation and poor social support [ 54 ]. Early evidence is mounting to suggest that lifestyle and environmental modification has the potential to prevent or even reverse ARD, especially when initiated early in the ARCD process [ 10 , 55 , 56 , 57 ].…”
Section: Population-level Observations and Evolutionary Theory Derive...mentioning
confidence: 99%